The Role of the Principal as an Educator in Developing Capability Teacher Information And Communication Technology - Sari, Putri Indah; Mustika, Dea; Wandri, Rizky (UIR PRESS, 2024)
The demands of teachers in this era require teachers to continue to develop with the times. It is the responsibility of the principal to help teachers improve their abilities. This study aims to determine the role, obstacles and solutions of the principal as an educator in developing the Information and Communication Technology skills of teachers at SD Negeri 109 Pekanbaru. This study used descriptive qualitative method. Data collection techniques using interviews, observation and documentation review. Testing the validity of the data using triangulation. Data analysis techniques namely data collection, data reduction, data presentation and drawing conclusions. The results showed that the principal had tried to carry out his role as an educator in developing teachers' ICT skills. The conclusion from the research results is that the role of the principal as an educator in developing teachers' ICT skills is carried out with strategies that have been prepared such as, involving teachers in all ICT-based training and providing opportunities for teachers to increase knowledge and skills, creating a conducive school atmosphere by completing infrastructure ICT and complement teaching materials by checking ICT teaching materials used by teachers in learning, providing guidance and advice at regular meetings or meetings and providing motivation such as giving praise to teachers who have contributed a lot to the school.